PENINGKATAN HASIL BELAJAR SEJARAH DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TIPE TEAMS GAMES TOURNAMENTS(TGT) PADA SISWA KELAS XI IPA2 MAN I MERANGIN - GUSRI YENI; DAHRIAL DAHRIAL (JURNAL ILMIAH MAKSITEK, 2023)
This Classroom Action Research (PTK) aims to improve history learning outcomes in class XI IPA2 MAN I Merangin students by using the Teams Games Tournaments (TGT) type learning model. The subjects of the study were students of class XI IPA2 which amounted to 32 students. This research was conducted in two cycles, each cycle consisted of four stages, namely planning, implementation, observation, and reflection. Data were collected through tests, observations, and questionnaires. The results showed that the application of TGT learning model can improve the learning outcomes of history in class XI IPA2 MAN I Merangin. In cycle I, the average score of the history test increased from 69.71 to 75.44 with an average learning completeness of 70.6%. In cycle II, the average score of the history test increased to 81.62 with an average learning completeness of 88.24%. In addition, there was an increase in student learning activities and motivation as well as an increase in social skills through cooperation in groups. Based on the results of this study, it can be concluded that the TGT learning model is effective for improving history learning outcomes in class XI IPA2 MAN I Merangin. Therefore, it is recommended for history teachers to use the TGT learning model in the learning process to improve student learning outcomes. In addition, this research can also be used as a reference for future researchers who want to conduct research on the use of TGT learning models in other subjects.